Smart City Maturity Analysis Based on COBIT 2019 and SNI ISO 37122:2019 - Ahkam, Syuaib; Ginardi, R. V. Hari (International Journal of Organizational Behavior and Policy, 2025)
In the current era of digital transformation, the development of Smart City is crucial for regions that want to improve public services, stimulate economic growth, and improve the quality of life of their citizens. West Sumbawa Regency, with its tourism and creative economy potential, has adopted the Smart City initiative. However, its effectiveness is hampered by suboptimal IT governance, limited digital infrastructure, and a lack of standardized integrated evaluation models. This study aims to analyze and assess the maturity of Smart City in West Sumbawa Regency by combining the COBIT 2019 framework for IT governance and SNI ISO 37122:2019 for smart city performance indicators. Using a mixed-methods approach—including a survey of 150 stakeholders for quantitative analysis and in-depth interviews with 50 key informants for qualitative analysis—as well as PLS-SEM analysis, capability maturity assessment, and GAP analysis, the results show that most IT governance processes are at maturity levels 2–3. This indicates a significant gap between existing IT governance practices and the achievement of Smart City indicators, particularly in aligning corporate objectives and risk management. The main contribution of this research is the development of an integrated evaluation model that provides a holistic evidence-based roadmap for local governments to formulate more effective Smart City policies to achieve sustainable smart city transformation.